Tethered Swimming for the Evaluation and Prescription of Resistance Training in Young Swimmers - Papoti, Marcelo; da Silva, Adelino S. R.; Kalva-Filho, Carlos Augusto; Araujo, Gustavo Gomes; Santiago, Vanessa; Martins, LuizEduardo Barreto; Cunha, Sérgio Augusto; Gobatto, Claudio Alexandre (International Journal of Sports Medicine, 2017)
The aims of the present study were 1) to evaluate the effects of 11 weeks of a typical free-swimming training program on aerobic and stroke parameters determined in tethered swimming (Study 1; n=13) and 2) to investigate the responses of tethered swimming efforts, in addition to free-swimming sessions, through 7 weeks of training (Study 2; n=21). In both studies, subjects performed a graded exercise test in tethered swimming (GET) to determine anaerobic threshold (AnT), stroke rate at AnT (SRAnT), peak force at GET (PFGET) and peak blood lactate ([La-]GET). Participants also swam 100-, 200- and 400-m lengths to evaluate performance. In Study 2, swimmers were divided into control (i. e., only free-swimming; GC [n=11]) and tethered swimming group (i. e., 50% of the main session; GTS [n=10]). The results of Study 1 demonstrate that AnT, PFGET, [La-]GET and 200-m performance were improved with free-swimming training. The SRAnT decreased with training. In Study 2, free-swimming performance and most of the graded exercise test parameters were not altered in either group. However, [La-]GET improved only for GTS. These results demonstrate that aerobic parameters obtained in tethered swimming can be used to evaluate free-swimming training responses, and the addition of tethered efforts during training routine improves the lactate production capacity of swimmers.
Keywords: blood lactate; anaerobic threshold; graded exercise test; performance; swimmers